Improvement of the Mechanical Properties of an Encrusting Tuff Treated with Sewage Sludge Bottom Ash and Lime - Khellou, Abderrezak; Abdeldjouad, Lokmane; Madun, Aziman; Firdaus, Mohd; Aminuddin K, Muhammad; Mokhtari, Abdessamed; Dehmani, Mohammed (International Journal of Sustainable Construction Engineering and Technology, 2024)
This work fits into the context of the valorization of local materials and industrial wastes. It aims to improve the mechanical strength of the encrusting tuff and reduce its water sensitivity through a mixed treatment with sewage sludge bottom ash (BA) and lime, which will incorporate this treated tuff into the Saharan pavements. Several formulations composed of encrusting tuff, BA, and lime were tested in the short- and long-term. The results obtained showed that the formulation TL4BA12 (84% tuff + 4% lime + 12% BA) has the best strength in simple compression (Rc) and indirect tension (Rtb), compared to tuff alone and the other tested formulations. This improvement in strength is observed for both short- and long-term. At 7 days, the Rc of TL4BA12 reached double that of tuff alone, and it was triple at 180 days. However, the Rtb of TL4BA12 was approximately four times that of tuff alone at 7 days and more than double at 180 days. The water sensitivity study revealed that the specimens prepared from the treated tuff remain intact after 24 h of immersion in water. In contrast, those prepared from tuff alone dissolved within minutes.